The Potential of Cookies Mantul (Calamansi and Bekatul/Rice Bran) as A Healthy Snack to Reduce Emesis Gravidarum in Pregnant Women - Yulyani, Linda; Purnama, Yetti (Poltekkes Kemenkes Jakarta III, 2025)
Nausea and vomiting in pregnancy (NVP) or emesis gravidarum (EG) is pregnancy discomfort experienced by 70-80% of pregnant women. In early pregnancy, pregnant women need to avoid chemical drugs as much as possible because of their potential teratogenic effects, so there is an increasing trend towards the use of alternative therapies. This research aimed to investigate the potential and influence of Cookies Mantul (a blend of calamansi and Bekatul/Rice Bran) on reducing the symptoms of nausea and vomiting in pregnant women in Trimester 1 (TM 1). This research was a Quasi-Experiment with a pre-post test control group design. There were 30 participants in this research, with 15 pregnant women in each group for the intervention and control groups. The data collected using the PUQE-24 Questionnaire and processed statistically using the Mann-Whitney test and the Wilcoxon test. The results of the statistical test showed that there was an effect of giving Mantul Cookies on reducing the level of nausea and vomiting in pregnant women in TM 1, with a p-value = 0.001. The statistical test for the conttrol group also indicated a significant effect on reducing nausea and vomiting following the pregnant women’s biscuit (p-value = 0.015). The results of the statistical test with the Mann-Whitney test showed that there was no difference in the level of nausea and vomiting in pregnant women after the intervention between the intervention and control groups, with a p-value = 0.240.